The Non-Place and the Unhomely in Ken Bugul’s Cacophonie - Anna Swoboda ([sic])
The aim of the article is to analyze the connection between non-places (as defined by Marc Augé) and unhomeliness (as understood by Homi Bhabha) in Cacophonie by Ken Bugul. The Senegalese writer has been best-known for her depiction of a postcolonial subject, torn between the Western and the African world. However, her last novel thus far, which concentrates on the trajectory of a Senegalese protagonist living in Benin, sheds new light on the notion of migrant identity. The heroine, Sali, does not belong anywhere. Just like most previous Bugulian protagonists, she is always in transit: her identity is one of an uprooted, fragmented subject. By examining the protagonist’s behavior in a public, archetypal non-place (an airport, a plane), as well in a private place (her house), the study strives to show Sali’s perpetual state of unhomeliness.Keywords: unhomeliness, non-place, postcolonial subject, Ken BugulThe postcolonial subject’s experience of migration and homecoming constitutes one of the most important motifs in the contemporary African Francophone literature. In the words of Irene Assiba d’Almeida, “even within globalization, which aims to annihilate space, the place from which we speak often influences how and of what we speak” (“Problématique de la mondialisation” 35). Ken Bugul, one of the most distinguished Senegalese writers, is often classified as a migritude author. Coined by Jaques Chevrier, the term – a portmanteau of the words migration and Négritude – expresses two contradictory desires and processes: migration and return to the home country (Malonga 1). The migritude is a type of self-writing, in which there exists “osmotic intensity between the authors and their female characters” (Malonga 5). According to the critic, Le Baobab fou – Ken Bugul’s first novel, published in 1982 – marks the beginning of migritude. Odile Cazenave notes that migrant female authors often construct literary characters whose identities are closely connected to their geographic location, entailing the modification of their status depending on their gender (“Roman africain” 50). She also argues that because of being marginalized, African Francophone female authors find themselves in a “paradoxically privileged position”, which allows them to conduct a significantly more thorough introspection and analysis of social problems (Femmes rebelles 25). Other scholars, like Ayo A. Coly, agree that the author’s gender is crucial in the analysis of postcolonial texts, as in the male dominated Francophone African migrant corpus, women are portrayed in a nationalist manner, as reproducers and guardians of national culture, which results in the creation of gender-specific narratives of home and nation. (XIV). However, Coly also argues that post-independence Francophone African migration “enacts the disappointment with and distrust of the postcolonial state but does not signify a transfer of identity allegiances and loyalties to a postnational third space” (XXIII). This claim seems to capture the essence of Ken Bugul’s writing.